Internal Functioning of Romanian Non-Profit Organizations – A New Governance Model And its Effect on Services and Community Relations - Claudia Petrescu; Martin Balogh; Natalia Monica Balogh; Paula Beudean (Transylvanian Review of Administrative Sciences, 2020)
The Romanian non-profit sector is experiencing an explosive growth, an increase of 60% in the last ten years due to the rapid economic and political changes taking place in the region. Currently, there are over 100,000 non-profits with approximately 40% of them being active (FDSC, 2017). This exploratory research aims to provide an understanding of the current Romanian non-profit governance model, the balance of power between board members and the executive director, and their implication on organizational relations with the community. The research analyzes the board – executive relation in the current social-economic context and the board’s involvement in the organization. The study also looks at how these affect the relations of the organizations with the community. Finally, the paper also analyzes how the financing model impacts the Romanian non-profit governance model. An online capacity-building assessment was used to collect the data. It was administered in the period August – October 2015 (for 55 active non-profit organizations with a 66% response rate).